2007
DOI: 10.1016/j.ajo.2006.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dry Eye Syndrome on Vision-Related Quality of Life

Abstract: DES is associated with a measurable adverse impact on several common and important tasks of daily living, further implicating this condition as an important public health problem deserving increased attention and resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
523
0
25

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 731 publications
(567 citation statements)
references
References 32 publications
19
523
0
25
Order By: Relevance
“…3 For activities in which relatively few persons participated in our sample (for example, only 731 of 3265 participants reported playing chess/cards), the sample size may not be sufficient to enable us to detect statistically significant differences. Differences in some of the daily activities performed by the participants, ethnicity of the participants, and study methodology could explain some discrepancy in findings across studies.…”
Section: Eyementioning
confidence: 99%
See 3 more Smart Citations
“…3 For activities in which relatively few persons participated in our sample (for example, only 731 of 3265 participants reported playing chess/cards), the sample size may not be sufficient to enable us to detect statistically significant differences. Differences in some of the daily activities performed by the participants, ethnicity of the participants, and study methodology could explain some discrepancy in findings across studies.…”
Section: Eyementioning
confidence: 99%
“…However, in that study, only three questions, instead of six, were used to assess dry eye symptoms. 3 Difficulty in performing the above activities may be related to prolonged gazing and reduced blinking due to greater visual demands in performing these activities and exposure to air-conditioning and low-humidity environments, which can result in instability and increased evaporation of the tear film leading to irregularity of the optical refracting surfaces. Previous studies have reported a significant reduction in the blinking rate associated with visual display terminal work, 22 reading, 8 and increased driving speed, 8,23 which can further result in instability of the tear film.…”
Section: Eyementioning
confidence: 99%
See 2 more Smart Citations
“…O olho seco é uma doença multifatorial da lágrima com dano potencial à superfície ocular, que resulta em desconforto, turvação visual e instabilidade do filme lacrimal (14) , com significativo impacto na qualidade de vida (28,29) .…”
Section: Discussionunclassified